Sacred Groves and Natural Sites Conservation for Tourism in Local Communities in Nigeria - Joy Nneka Uchenye Ejikeme; Uche Uwaezuoke Okonkwo (African Journal of Hospitality, Tourism and Leisure, 2022)
The purpose of this study is to examine the potentials of sacred groves and natural sites in order to harness them for tourism in local communities of Nigeria. Three communities in Inyi town were chosen as case studies: Umuome, Enugwu-Inyi, and Alum, using a purposive sampling technique. An ethnographic data collection method was adopted which involves in-depth interviews and direct observation. Grove locations were located and mapped using a geographic information system (GIS) in the research area. The secondary data was obtained from scholarly journals, books, theses, etc. The findings showed that the sacred groves and natural sites had exceptional value for cultural and eco-tourism. Existing literature reveals that no study has investigated the tourism dimension of the sacred groves. The implication of the study is that tourism aids in the preservation of sites' integrity. It shields the sacred groves from deteriorating and going into extinction. While this research will help researchers at the universities and research institutions that are seeking to carry out related research, it is more important to the government in that it will help other policymakers adopt a policy that promotes tourism in the sacred groves. Finally, the study recommends that sacred groves should be utiliz for tourism since it is a superior conservation alternative.